Effects of dribbling restrictions in small-sided games on aerobic and anaerobic fitness in youth basketball players - Li, Mingbang; Tan, Liang; Wu, Hong; Wu, Jianwei (Frontiers in Physiology, 2025)
IntroductionImposing constraints such as limiting dribbling in smallsided games (SSGs) is known to increase physiological and locomotor demands. However, the long-term effects on physical adaptations remain unexplored. This experimental study aimed to compare the impact of free-play SSGs (freeD) and limited-dribbling SSGs (limitedD) in SSGs on the aerobic and anaerobic adaptations of youth basketball players.MethodsForty-five youth basketball players (aged 15.7 ± 0.6 years, with 4.2 ± 0.7 years of experience) were randomly assigned to two experimental groups (freeD and limitedD) and a control group (not exposed to SSG interventions). During the eight-week intervention, the experimental groups participated in additional SSG sessions twice a week, with session work time durations ranging from 12 to 16 min. Both experimental groups followed identical SSG formats, court dimensions, and training regimens, with the only difference being that one group participated in free play while the other group was prohibited from dribbling during progression. Aerobic capacity was assessed using the Yo-Yo Intermittent Recovery Test Level 1 (YYIRT), while the 30-second Wingate Test measured peak power output (PPO) and average power output (APO) at baseline and post-intervention. Statistical analysis was conducted using a mixed ANOVA to examine the interactions between time and group.ResultsComparisons of YYIRT between groups at post-intervention revealed that limitedD performed significantly better than both freeD (p = 0.035; d = 1.038) and the control group (p < 0.001; d = 2.050), while freeD also showed significantly better performance (p = 0.021; d = 0.082) than the control group. Regarding PPO, limitedD was significantly better than the control group (p = 0.043; d = 0.943). Finally, for APO, limitedD was significantly better than both freeD (p = 0.043; d = 0.928) and the control group (p < 0.001; d = 1.793), while freeD also exhibited significantly better performance than the control group (p = 0.046; d = 0.036).ConclusionsLimiting dribbling in basketball SSGs is more effective than free play. This makes it a potentially valuable strategy for designing SSGs in basketball training. Coaches may consider incorporating limited-dribbling conditions into SSGs to boost the intensity of training sessions, improve cardiovascular endurance, and enhance anaerobic power.